1990
DOI: 10.1002/1097-0142(19901215)66:12<2583::aid-cncr2820661222>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of type IV collagen and laminin immunoreactivity in urothelial carcinomas of the bladder

Abstract: Invasion of a carcinoma involves the degradation and penetration of the subepithelial basement membrane (BM). This phenomenon might be used for histopathologic evaluation of neoplasms of the bladder. The authors studied the clinicopathologic data and tissue specimens of 125 cases of urothelial carcinomas collected prospectively. Penetration of the BM was evaluated by immunohistochemical staining of the BM components laminin and type IV collagen. The use of this parameter as a prognostic indicator in bladder ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 16 publications
3
28
0
1
Order By: Relevance
“…It has also been shown that BM disruption in bladder carcinomas correlates with lower 5-year survival rate, higher tumour stage, higher histological grade and tumour ploidy (Schapers et al, 1990). In this material BM disruption was also associated with positive p53 immunohistochemistry, further emphasising the fact that p53 positive bladder carcinomas are of a more aggressive nature.…”
Section: Discussionsupporting
confidence: 61%
“…It has also been shown that BM disruption in bladder carcinomas correlates with lower 5-year survival rate, higher tumour stage, higher histological grade and tumour ploidy (Schapers et al, 1990). In this material BM disruption was also associated with positive p53 immunohistochemistry, further emphasising the fact that p53 positive bladder carcinomas are of a more aggressive nature.…”
Section: Discussionsupporting
confidence: 61%
“…Previously, the integrity of the UBM was demonstrated using polyclonal and monoclonal antibodies to type IV collagen and/or laminin and was used to establish a relationship between superficial and invasive transitionalcell carcinomas, the latter often being associated with the loss of basement membrane staining [4,15,20]. Normally the UBM is continuous, with colocalization of type IV collagen and/or laminin occuring in normal and nonmalignant inflammation specimens [2,5], although an unspecified, indistinct staining pattern was found in 1 of 17 normals associated with inflammatory infiltrates in an earlier study [4].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that the metastatic potential of primary tumors correlates with the degree of BM loss (Barsky et al, 1983;Havenith et al, 1988;Schapers et al, 1990). An altered ECM, in particular the loss of collagen expression, is characteristic of the latter stages of malignant progression and was shown to coincide with the acquisition of an invasive phenotype (Tanaka et al, 1997;Nakano et al, 1999;Catusse et al, 2000).…”
Section: Introductionmentioning
confidence: 99%